2009
DOI: 10.1177/112067210901900203
|View full text |Cite
|
Sign up to set email alerts
|

LASIK and PRK in Refractive Accommodative Esotropia: A Retrospective Study on 20 Adolescent and Adult Patients

Abstract: The treatment of fully refractive accommodative esotropia with excimer laser was found effective and safe, even in young or adolescent patients. More studies are needed to increase the patient experience and extend the follow-up period in order to evaluate the stability of these results over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Several small studies have reported the efficacy of LASIK to correct accommodative esotropia in adult patients [27 ,28 ,29]. Accommodative esotropia is improved with correction of hyperopia, but late onset of regression of hyperopic correction may occur [28 ]. All patients treated in one series had purely accommodative esotropia preoperatively [28 ].…”
Section: Corneal Refractive Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…Several small studies have reported the efficacy of LASIK to correct accommodative esotropia in adult patients [27 ,28 ,29]. Accommodative esotropia is improved with correction of hyperopia, but late onset of regression of hyperopic correction may occur [28 ]. All patients treated in one series had purely accommodative esotropia preoperatively [28 ].…”
Section: Corneal Refractive Proceduresmentioning
confidence: 96%
“…In addition, target refractive status must be adjusted if esophoria has been eliminated with the use of bifocals in patients with high accommodative convergence to accommodation ratios. Also, patients with accommodative esotropia require correction of their cycloplegic hyperopic correction rather than their latent hyperopia to control their strabismus [28 ]. Several small studies have reported the efficacy of LASIK to correct accommodative esotropia in adult patients [27 ,28 ,29].…”
Section: Corneal Refractive Proceduresmentioning
confidence: 99%
“…Many authors have shown refractive surgery can effectively treat accommodative esotropia [32 ,33-35]. Only a few reports have specifically targeted children and adolescents for refractive surgery to treat accommodative esoptropia [43][44][45]. Phillips et al [45] reported on 15 patients with an average age of 13.9 years old (range:9.1-18.8) with average hyperopia of þ5.35 diopters.…”
Section: Refractive Surgery and Strabismusmentioning
confidence: 98%
“…Studies have reported good results with LASIK and PRK in fully refractive accommodative esotropia as well as the accommodative component of partially accommodative esotropia. 5,6,7 Magli et al 5 did a retrospective study on 20 adoloscent and adult patients with refractive accommodative esotropia and found that over a follow up of 30.2 months, 40% were orthophoric for distance and near and the remaining were well within acceptable limits of residual deviation. Their mean correction was +4.62D (Range +2.25-+7.75DS SD 4.52).…”
Section: Refractive Accommodative Esotropiamentioning
confidence: 99%